Deliberate ignorance in project risk management - Kutsch, Elmar; Hall, Mark L. (Elsevier Science B.V., Amsterdam., 2010)
The management of project risk is considered a key discipline by most organisations involved in projects. Best practice project risk management processes are claimed to be self-evidently correct. However, project risk management involves a choice between which information is utilized and which is deemed to be irrelevant and hence excluded. Little research has been carried out to ascertain the manifestation of barriers to optimal project risk management such as 'irrelevance'; the deliberate inattention of risk actors to risk. This paper presents the results of a qualitative study of IT project managers, investigating their reasons for deeming certain known risks to be irrelevant. The results both confirm and expand on Smithson's [Smithson, M., 1989. Ignorance and Uncertainty. Springer-Verlag, New York] taxonomy of ignorance and uncertainty and in particular offer further context related insights into the phenomenon of 'irrelevance' in project risk management. We suggest that coping with 'irrelevance' requires defence mechanisms, the effective management of relevance as well as the setting of, and sticking to priorities. (C) 2009 Elsevier Ltd and IPMA. All rights reserved.